Pengaruh Pelatihan Peace and Love terhadap Pengetahuan dan Keterampilan Penanganan Cedera Ankle Sprain pada Anggota Knc-Emergency - Raditya Sohan Harizega; Wahyu Rima Agustin; Anissa Cindy Nurul Afni (Universitas Muhammadiyah Klaten, 2025)
Ankle sprain is a musculoskeletal injury due to excessive tension or tearing of the ankle ligaments. Ankle sprain injuries can be managed with the PEACE and LOVE approach, which is an injury management method that not only focuses on the improvement but also considers aspects of injury recovery to increase knowledge and awareness of injury and recovery of psychological trauma post-injury. KNC-Emergency is an organization that plays an active role in handling medical teams, therefore it is important to develop medical knowledge and skills in first aid for injuries. Purpose to find out the application effect of the PEACE and LOVE training on the knowledge and skills of ankle sprain management in KNC-Emergency members. The research method used the quasi-experiment, the sampling technique used purposive sampling using the Slovin formula for 38 KNC-Emergency members. The PEACE and LOVE training was conducted over two meetings using the measurement tool of a questionnaire sheet to measure knowledge and an observation sheet to measure ankle sprain injury management skills using the PEACE and LOVE approach. The bivariate result using the Wilcoxon test pre and post training showed a p-value of 0.000 (p-value < 0.05). The PEACE and LOVE training is effective to improve knowledge and skills of ankle sprain management in KNC-Emergency members